2021
DOI: 10.17973/mmsj.2021_12_2021116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shape of Pressure Vessel Shell on Bolt Working Load and Tightness

Abstract: The area of flange joints with gasket includes many types of pressure vessels, which are mainly defined by the purpose of use and specific load conditions. These differences in definitions caused the existence of many types of pressure vessels with different shell shapes. Calculations of basic shapes are defined by standards. However, in some fields of engineering practice, these shapes are atypical. The article discusses the issue of circular sealed flange joints with a nonstandard shape of the pressure chamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the area of the circular joints of pressure vessels, it turned out that the asymmetry of the connected envelope also has a significant influence on the magnitude of the operating force in the bolt. A detailed description of this issue is given in [6].…”
Section: Description Of the Basic Approach To Solving Bolted Jointsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the area of the circular joints of pressure vessels, it turned out that the asymmetry of the connected envelope also has a significant influence on the magnitude of the operating force in the bolt. A detailed description of this issue is given in [6].…”
Section: Description Of the Basic Approach To Solving Bolted Jointsmentioning
confidence: 99%
“…The size of the force increase in the bolt ∆F S (see Figure 3) from the operational force is not dependent only on the stiffnesses C S and C F . Previous research in the field of flanges (especially circular) joints has shown that the behavior of the load force in the bolt is also influenced by the position of the point of the operational force, see [7] (p. 161) and [6]. This location may be subject to change during operation, especially in the case of joints where significant deformations occur due to the operating load (e.g., the flange joints of thin-walled vessels).…”
Section: Description Of the Basic Approach To Solving Bolted Jointsmentioning
confidence: 99%
See 1 more Smart Citation
“…In none of the articles mentioned above are the uniformity of axial forces and therefore also the uniformity of stresses and pressures of the clamping sleeve addressed. Very often, the tightening procedure for flanged sealing surfaces is solved [10,11], where, of course, the uniformity of the axial force in the bolts has an influence on the uniformity of the pressure acting on the seal, which is needed for the correct functioning of the seal. It is at this point that the similarity between this flanged sealant joints and a clamping joint becomes apparent, where the pressure acting on the tapered surfaces and cylindrical surfaces to transfer the load is essential to the correct function of the joint.…”
Section: Uniformity With Respect To the Tightening Sequencementioning
confidence: 99%